2017
DOI: 10.1186/s12929-017-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mesenchymal stem cells into cardiomyocytes is regulated by miRNA-1-2 via WNT signaling pathway

Abstract: BackgroundBone marrow derived stem cells (BMSCs) have the potential to differentiate into cardiomyocytes, but the rate of differentiation is low and the mechanism of differentiation is unclear completely. Here, we aimed to investigate the role of miR1-2 in differentiation of mouse BMSCs into cardiomyocyte-like cells and reveal the involved signaling pathways in the procedure.MethodsMouse BMSCs were treated with miR1-2 and 5-azacytine (5-aza). The expression of cardiac cell markers: NKx2.5, cTnI and GATA4 in BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
0
53
0
1
Order By: Relevance
“…In recent years, MSC have also been utilized for the generation of mesenchymal as well as non-mesenchymal cell lineages, including neuron-like, hepatocyte-like, and cardiac-like cells [6][7][8][9][10]. Despite these promising results, the differentiation of human MSC into fully mature cardiomyocytes bearing all their respective phenotypical and functional characteristics is difficult [11][12][13][14][15]. As MSC are located in various tissues, they represent a heterogeneous progenitor cell population dependent on the tissue source and the individual donor [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, MSC have also been utilized for the generation of mesenchymal as well as non-mesenchymal cell lineages, including neuron-like, hepatocyte-like, and cardiac-like cells [6][7][8][9][10]. Despite these promising results, the differentiation of human MSC into fully mature cardiomyocytes bearing all their respective phenotypical and functional characteristics is difficult [11][12][13][14][15]. As MSC are located in various tissues, they represent a heterogeneous progenitor cell population dependent on the tissue source and the individual donor [16].…”
Section: Introductionmentioning
confidence: 99%
“…Small non-coding RNAs, like microRNAs (miRNA) and chemically modified messenger RNA (mRNAs) allow the manipulation of cell behavior for a limited period of time, e.g., triggering (trans)-differentiation by activation of lineage-specific molecular pathways. Some studies have already shown that alteration of gene expression using selected miRNAs can induce cardiac differentiation of MSC to a small extent [15,25,26], while data about mRNA-based cardiac reprogramming is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA or miR) is a class of small non-encoding RNA molecules (18)(19)(20)(21)(22) nucleotides) that bind with the 3'-untranslated region (UTR) of mRNA to inhibit its translation (15). miRNA plays important regulatory roles in post-transcriptional levels of genes, and widely participates in the proliferation, aging, apoptosis, migration, differentiation, and drug resistance of cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-33b-5p enhances the sensitivity of gastric cancer cells to chemotherapeutic drugs and improves their clinical efficacy (19). Of note, Wnt/β-catenin signaling pathway that is regulated by Dact2, is also regulated by various miRNA molecules (20). Therefore, miRNA is likely to be involved in the regulation of Dact2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…MiRs have also been proven to be important translational determinants of the SC fate [507]. A combination of 5-azacytine and miR-1 overexpression induces the expression of cardiac specific genes like Nkx2.5 and troponin I via activation of the Wnt/β-catenin signaling pathway in MSCs [508,509]. In addition, miR-133a and miR-499 were shown to promote the commitment of MSCs and CSCs/CPCs towards a cardiomyogenic lineage [510][511][512][513].…”
Section: Genetic Sc Modificationsmentioning
confidence: 99%